2020
DOI: 10.1371/journal.pone.0237479
|View full text |Cite
|
Sign up to set email alerts
|

Different types of cartilage neotissue fabricated from collagen hydrogels and mesenchymal stromal cells via SOX9, TGFB1 or BMP2 gene transfer

Abstract: Objective As native cartilage consists of different phenotypical zones, this study aims to fabricate different types of neocartilage constructs from collagen hydrogels and human mesenchymal stromal cells (MSCs) genetically modified to express different chondrogenic factors. Design Human MSCs derived from bone-marrow of osteoarthritis (OA) hips were genetically modified using adenoviral vectors encoding sex-determining region Y-type high-mobility-group-box ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…We and others showed that COL type I hydrogels enhance chondrogenic differentiation and maintenance of chondrogenic phenotype in seeded MSCs in vitro, especially when paired with specific growth factors or gene transfer [ 19 , 53 , 55 ]. However, research has shown that both COL I-based scaffolds promote chondrogenesis in seeded MSCs with a possible superior synthesis of cartilage-specific ECM components but no significant differences in the expression of chondrogenic marker genes [ 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We and others showed that COL type I hydrogels enhance chondrogenic differentiation and maintenance of chondrogenic phenotype in seeded MSCs in vitro, especially when paired with specific growth factors or gene transfer [ 19 , 53 , 55 ]. However, research has shown that both COL I-based scaffolds promote chondrogenesis in seeded MSCs with a possible superior synthesis of cartilage-specific ECM components but no significant differences in the expression of chondrogenic marker genes [ 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, we and others showed that gene transfer of different members of the TGF-ß superfamily led to enhanced chondrogenesis of BMSCs seeded in hydrogels in vitro and in vivo [ 19 , 99 , 100 , 101 , 103 , 104 , 105 , 106 ]. Xia et al found that adenoviral gene transfer of TGF-ß1 (encoded by TGFB1 ) to BMSCs encapsulated in PGA hydrogels led to enhanced chondrogenesis in vivo [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of genes have been identified as potential chondrogenic markers, among which sex determining region Y-box9 (Sox9) gene has been confirmed to be a key gene in cartilage formation [8,9] . The role of Sox9 gene in cartilage differentiation is achieved by inhibiting Beta catenin (β-catenin) gene and there is a complex relationship between them.…”
mentioning
confidence: 99%